2006
DOI: 10.3127/ajis.v13i2.47
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Data: methods for understanding mobile technology use

Abstract: Mobile devices, applications and services have become integrated into people's daily lives on a personal and professional level. Although traditional research methods are being used to understand the use of mobile devices and applications, methodological challenges still exist. Researchers have responded to these challenges in a variety of ways, with an emphasis on developing methods that enable new ways of accessing, making available and collecting data about mobile technology use. This paper identifies, defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 45 publications
0
58
0
3
Order By: Relevance
“…Participant observation is difficult in domestic environments (eg Hagen et al 2005;Bratteteig et al 2013). As an alternative, a series of probe kits were designed and the first of these distributed at the workshop.…”
Section: Probesmentioning
confidence: 99%
“…Participant observation is difficult in domestic environments (eg Hagen et al 2005;Bratteteig et al 2013). As an alternative, a series of probe kits were designed and the first of these distributed at the workshop.…”
Section: Probesmentioning
confidence: 99%
“…The emaildiary provides an opportunity to explore the complexity of human behaviour (Harvey 1993), including the differences and similarities created by temporal dynamics (Bolger et al, 2003) and tracking changes and similarities between participant groups over a period of time (Bell 1998). It is also a research method that harnesses and reflects the modern mobile culture (Murry 2009;Hagen et al, 2005), benefits from frequent updates (Barrett and Barrett, 2001), takes advantage of the research opportunities presented by the internet (Hanna, 2012), and allows for a more equal relationship between the researcher and the participant (Rappaport and Stewart, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Mobile culture and diary research Murry (2009) considered that social scientists need to research methodologies that harness the mobile culture which Hagen et al (2005) believed should enable diarists to complete their entries either in the office, at home or on the move, using mobile technology. In his analysis of the use of Internet technologies such as Skype, Hanna (2012) suggested that further research was needed on the use of technology, whilst Evans et al (2008) believed that using the internet is a viable conduit to help overcome problems associated with distance and access.…”
Section: Problems With Diariesmentioning
confidence: 99%
“…The author explored how to use the user identifier provided by wireless carriers in the mobile clickstream analysis 4) . Methodological challenges to understand the use of mobile devices and applications still exist 5) . It is also applied to the mobile clickstream by Halvey 6) .…”
Section: Related Workmentioning
confidence: 99%